Marketing Strategy for Madrasa Quality in Increasing Interest in Education Customers (Multisite Study at Madrasah Aliyah Negeri 1 Tulungagung and Madrasah Aliyah Negeri 1 Kota Kediri) - Nur Alamsyah, Mochamad; Masrokan, Prim; Efendi, Nur (International Journal of Educational Research & Social Sciences, 2024)
This dissertation is based on the results of the researcher's observations regarding the conditions of madrasa marketing at Madrasah Aliyah Negeri 1 Tulungagung and Madrasah Aliyah Negeri 1 Kota Kediri and its role in efforts to increase the interest of educational customers. The problem formulation in this research is: (1) How does madrasa branding increase the interest of educational customers at Madrasah Aliyah Negeri 1 Tulungagung and Madrasah Aliyah Negeri 1 Kota Kediri? (2) How does madrasa differentiation increase the interest of educational customers? (3) How does madrasa positioning increase the interest of educational customers? (4) How does madrasa direct marketing increase the interest of educational customers? This dissertation aims to find and describe madrasa quality marketing strategies in the form of branding, differentiation, positioning, and direct marketing in increasing the interest of educational customers at Madrasah Aliyah Negeri 1 Tulungagung and Madrasah Aliyah Negeri 1 Kota Kediri, where the researcher conducted qualitative research and is a type of research with a multisite research design. Data collection techniques were carried out using (1) in-depth interviews, (2) participant observation, and (3) documentation. Data analysis was carried out in two ways, namely single site analysis with data collection, data condensation, data display and drawing conclusion steps, then continued with cross-site analysis. Checking the validity of the data is carried out using credibility, transferability, dependability and confirmability tests. The results of this research found that: The marketing strategy for madrasa quality in increasing the interest of educational customers is carried out by: a) branding, displaying the basic character of the madrasa in the form of mottos and slogans; b) differentiation, creating madrasas that have special services; c) positioning, implementing early admission patterns for new students and various levels of student admission schemes; d) direct marketing, direct marketing through the school website, promotion of madrasa success both in competitions at various levels and acceptance at universities as well as selection of outstanding female students through the student achievement program, and e) selected door to door, going directly to find and recruit students with achievement. Keywords: Marketing Strategy, Madrasa Quality, Educational Customer Interest.